Estimates of the population prevalence of injection drug users among hispanic residents of large US metropolitan areas. - Pouget, Enrique R; Friedman, Samuel R; Cleland, Charles M; Tempalski, Barbara; Cooper, Hannah L F (Journal of urban health : bulletin of the New York Academy of Medicine, 2012)
Little information exists on the population prevalence or geographic distribution of injection drug users (IDUs) who are Hispanic in the USA. Here, we present yearly estimates of IDU population prevalence among Hispanic residents of the 96 most populated US metropolitan statistical areas (MSAs) for 1992-2002. First, yearly estimates of the proportion of IDUs who were Hispanic in each MSA were created by combining data on (1) IDUs receiving drug treatment services in Substance Abuse and Mental Health Services Administration (SAMHSA)'s Treatment Entry Data System, (2) IDUs being tested in the Centers for Disease Control and Prevention (CDC) HIV-Counseling and Testing System, and (3) incident AIDS diagnoses among IDUs, supplemented by (4) data on IDUs who were living with AIDS. Then, the resulting proportions were multiplied by published yearly estimates of the number of IDUs of all racial/ethnic groups in each MSA to produce Hispanic IDU population estimates. These were divided by Hispanic population data to produce population prevalence rates. Time trends were tested using mixed-effects regression models. Hispanic IDU prevalence declined significantly on average (1992 mean = 192, median = 133; 2002 mean = 144, median = 93; units are per 10,000 Hispanics aged 15-64). The highest prevalence rates across time tended to be in smaller northeastern MSAs. Comparing the last three study years to the first three, prevalence decreased in 82% of MSAs and increased in 18%. Comparisons with data on drug-related mortality and hepatitis C mortality supported the validity of the estimates. Generally, estimates of Hispanic IDU population prevalence were higher than published estimates for non-Hispanic White residents and lower than published estimates for non-Hispanic Black residents. Further analysis indicated that the proportion of IDUs that was Hispanic decreased in 52% and increased in 48% of MSAs between 2002 and 2007. The estimates resulting from this study can be used to investigate MSA-level social and economic factors that may have contributed to variations across MSAs and to help guide prevention program planning for Hispanic IDUs within MSAs. Future research should attempt to determine to what extent these trends are applicable to Hispanic national origin subgroups.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; African Continental Ancestry Group; Centers for Disease Control and Prevention (U.S.); Data Collection; European Continental Ancestry Group; Hepatitis C; Hispanic Americans; Humans; Middle Aged; New England; Prevalence; Reproducibility of Results; Substance Abuse, Intravenous; United States; United States Substance Abuse and Mental Health Services Administration; Urban Population; Young Adult